2010
DOI: 10.1517/17425255.2010.482929
|View full text |Cite
|
Sign up to set email alerts
|

Using drug probes to monitor hepatic drug metabolism in critically ill patients: midazolam, a flawed but useful tool for clinical investigation of CYP3A activity?

Abstract: Critically ill patients are difficult to manage but methods are now available for investigation of complex interrelationships that complicate the care and management of these patients with the potential to improve safety, efficacy and outcome, particularly for drug administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…and oral ALF, and had free access to food and water thereafter. Venous blood samples were obtained 0, 2, 5, 10,20,30,45,60,90,120,180,185,190,195,210,225,240,270, 300, 360, 420, 480, 540, 600, and 660 min after i.v. d 0 -ALF (corresponding to 5, 10, 15, 30, 45, 60, 90, 120, 180, 240, 300, 360, 420, and 480 min after oral d 3 -ALF) on sequential dosing session days and at 0, 2, 5, 10, 20, 30, 45, 60, 90, 120, 150, 180, 210, 240, 300, 360, 420, and 480 min after i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and oral ALF, and had free access to food and water thereafter. Venous blood samples were obtained 0, 2, 5, 10,20,30,45,60,90,120,180,185,190,195,210,225,240,270, 300, 360, 420, 480, 540, 600, and 660 min after i.v. d 0 -ALF (corresponding to 5, 10, 15, 30, 45, 60, 90, 120, 180, 240, 300, 360, 420, and 480 min after oral d 3 -ALF) on sequential dosing session days and at 0, 2, 5, 10, 20, 30, 45, 60, 90, 120, 150, 180, 210, 240, 300, 360, 420, and 480 min after i.v.…”
Section: Discussionmentioning
confidence: 99%
“…1 Considerable effort has been expended toward identifying and developing an in vivo probe for assessment of human hepatic and intestinal CYP3A activity (or phenotype), prediction of CYP3A-dependent drug metabolism, and individualized dosing of CYP3A drugs with narrow therapeutic indexes. [6][7][8][9][10] US Food and Drug Administration regulations for new drug development require clinical assessment of potential drug interactions and, preferably, their consequences. Clinically, there is profound interest in using CYP3A activity assessment to predict optimal dosing, improve therapeutic efficacy, and minimize adverse drug effects.…”
mentioning
confidence: 99%
“…People homozygous for CYP3A5*3 produce a non-functioning CYP3A5 protein which is the predominant form in 80% of Caucasian populations. The wild type predominates in Sub-Saharan Africans [38], 60% are homozygous for CYP3A5*1 . Other CYP enzymes involved in drug metabolism in humans include CYP1A, CYP2C19, CYP2C9 and CYP2D6, together they account for 80% of all drug metabolism [39].…”
Section: Potential Mechanisms Of How Aki Affects Non-renal Drug Clearmentioning
confidence: 99%
“…It should be mentioned, however, that one study reported a decreased clearance of the CYP3A substrate midazolam 1-12 months after transplantation compared with 7 days after transplantation (de Jonge et al, 2015). Although midazolam is considered a gold standard CYP3A probe drug, it is also highly bound to plasma proteins (Kirwan et al, 2010). Albumin levels are reported to be reduced in patients with chronic kidney disease and after recent surgery (Meijers et al, 2008;Hubner et al, 2016) and increase with time after transplantation (Størset et al, 2014).…”
Section: Discussionmentioning
confidence: 99%